2004
DOI: 10.1176/appi.ps.55.11.1250
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Severity, and Co-occurrence of Chronic Physical Health Problems of Persons With Serious Mental Illness

Abstract: Risk adjustment for physical health is essential when setting performance standards or cost expectations for mental health treatment. Excluding persons with chronic health problems from mental health service evaluations restricts generalizability of research findings and may promote interventions that are inappropriate for many persons with serious mental illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
178
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(193 citation statements)
references
References 37 publications
(25 reference statements)
12
178
3
Order By: Relevance
“…People with severe mental illnesses such as schizophrenia experience disparate early morbidity and mortality due to smoking-related diseases. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] This group is therefore an important target for prevention and cessation treatment efforts.…”
Section: Introductionmentioning
confidence: 99%
“…People with severe mental illnesses such as schizophrenia experience disparate early morbidity and mortality due to smoking-related diseases. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] This group is therefore an important target for prevention and cessation treatment efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Adults with mental illness are at higher risk for physical health problems than those without mental illness [1][2][3], but less is known about Correspondence to: Gregory A. Aarons, Ph.D., Associate Professor of Psychiatry, University of California, San Diego, Child & Adolescent Services Research Center, 3020 Children's Way, MC-5033, San Diego, CA 92123-4282, Tel: 858.966.7703 ext. 3550, Fax: 858.966.7704, gaarons@ucsd.edu.…”
Section: Introductionmentioning
confidence: 99%
“…We focus on health problems shown to be related both directly and indirectly to mental health problems, by either a direct impact on the immune system or through altered health behaviors. These disorders also tend to be more common in adolescents, as opposed to physical health problems shown to be related to mental health problems in adults, such as cardiovascular disorders or Type II diabetes [1][2][3]. …”
mentioning
confidence: 99%
“…Dickey et al reviewed 11,185 adult Medicaid beneficiaries treated for severe mental illness and found that 56 percent had one and 26 percent had more than one of the following: diabetes, hypertension, heart disease, asthma, gastrointestinal disorders, infections of the skin and subcutaneous tissue, malignant neoplasms, and acute respiratory disorders [7]. Similarly, Jones et al analyzed Medicaid claims data for 147 individuals with severe mental illness and found that 74 percent had one diagnosis of chronic health problems, while 50 percent had two or more diagnoses [8]. Sokal et al studied 200 psychiatric outpatients with schizophrenia and affective disorders and found that they had significantly elevated odds of diabetes, lung diseases, and liver problems compared with matched subsets of individuals from the general population [9].…”
Section: Introductionmentioning
confidence: 99%